Enhanced Degradation of Juvenile Hormone Promotes Reproductive Diapause in the Predatory Ladybeetle Coccinella Septempunctata - Li, Yu-Yan; Chen, Jun-Jie; Liu, Meng-Yao; He, Wei-Wei; Reynolds, Julie A; Wang, Ya-Nan; Wang, Meng-Qing; Zhang, Li-Sheng (Frontiers in Physiology, 2022)
Improved knowledge on the regulation of reproductive diapause in Coccinella septempunctata, an important predator of aphids, is crucial for improving shelf-life and mass production of the ladybeetles. In many insects, the absence of juvenile hormone (JH) is a central regulator of reproductive diapause. JH is principally degraded by JH esterase (JHE) and JH epoxide hydrolase (JHEH). Previous studies have shown that genes encoding these enzymes were upregulated in early diapause of C. septempunctata, but whether increased JH degradation contributes to the reduction of JH levels and facilitates reproductive diapause remains unknown. Here, we investigate the role of JH and JH degradation genes during reproductive diapause in C. septempunctata females. Applying methoprene, a JH analogue, to the diapause preparation females clearly elevated JH signaling and reversed diapause program, suggesting that a lower level of JH is critical for the induction of reproductive diapause in the ladybeetle. Full-length cDNA sequences of JHE and JHEH were cloned and characterized, and their deduced proteins contain all the conserved active domains and typical motifs as identified in other insects. The expressions of JHE and JHEH were both significantly increased in diapause preparation and remained at a high level for a period throughout diapause, and then decreased after the termination of diapause. Knocking down these JH degradation genes clearly increased the expression levels of JH-inducible genes Krüppel-homolog 1 (Kr-h1) and vitellogenin (Vg), indicating an elevated JH level. Simultaneously, silencing JH degradation genes distinctly reduced diapause-related features and promotes reproduction, indicated by accelerated ovary growth, yolk deposition, and suppressed lipid accumulation. These results indicate that the enhanced JH degradation plays a critical role in regulating reproductive diapause of Coccinella septempunctata.